N-Nornuciferine Promotes Human Non-Small Cell Lung Cancer A549 Cells Apoptosis via miR-361-3p/TRAF2/JNK Axis - Chengxiang Wang; Lin Bai (Middle East Journal of Cancer)
Background: N-Nornuciferine (N-NF) is an aporphine alkaloid in lotus leaf with a good resource for obtaining the biologically active substances with antioxidant properties. The purpose of this study was to explore the effect of N-NF on cell viability and apoptosis in A549 cells in vitro culture and to explore its mechanism of action.Method: In this experimental study, we cultured A549 cells in vitro and added different concentrations of N-NF for intervention to explore cell apoptosis and its mechanism. Cell viability was detected by CCK-8, and cell apoptosis level was detected by flow cytometry. The mechanism of action of N-NF was explored by regulating the expression of miR-361-3p. The data were analyzed using the one-way analysis of variance (ANOVA) technique in SPSS 22.0 software, with statistical significance set at a level of P < 0.05.Results: The study results showed that N-NF could significantly inhibit the viability of A549 cells and promote apoptosis. Using dual-luciferase reporter gene and molecular biology detection experiments, it was found that N-NF inhibits the viability of A549 cells through inhibiting the expression of miR-361-3p and promoting the TRAF2/JNK pathway.Conclusion: This study provides a basis for the development of N-NF as an anticancer drug and explains its mechanism of promoting apoptosis of A549 cells.